The Association between Vitamin D and Wheezing - Hussain, Murtaza; Malik, Qudratullah; Khan, Qamar uz Zaman; Bashir, Junaid; Abbas, Muhammad; Ijaz, Maryam (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the association between vitamin D status and recurrent wheezing. Study Design: Comparative cross-sectional study. Place and Duration of Study: Department of Paediatrics, Pak Emirates Military Hospital (PEMH), Rawalpindi Pakistan, from Aug 2019 to Aug 2020. Methodology: Sixty infants with recurrent wheezing and 60 healthy age-matched infants without acute or chronic illness were inducted into the study. 25 (OH) Vitamin D, immunoglobulin E (IgE) levels and eosinophil counts were measured. In addition, data were analyzed to find the association of vitamin D levels with recurrent wheezing. Results: In the Control-Group, the mean 25 (OH) vitamin D levels were 25.90±7.57 ng/ml and in the Recurrent Attack- Group was 13.90±4.63 ng/ml (p= 0.02). The mean IgE levels of the Control-Group were 22.80±2.67 IU/ml, and the Recurrent Attack-Group was 149.20±30.60 IU/ml (p=0.001). Eosinophil count in Recurrent Attack-Group was 150.40±23.11 cells/uL and 338.95±33.50 cells/uL in Control-Group respectively (p= 0.08) Conclusion: There is a strong association between low vitamin D levels and recurrent wheezing.